2018
DOI: 10.3762/bjoc.14.49
|View full text |Cite
|
Sign up to set email alerts
|

Sequential Ugi reaction/base-induced ring closing/IAAC protocol toward triazolobenzodiazepine-fused diketopiperazines and hydantoins

Abstract: A practical three-step protocol for the assembly of triazolobenzodiazepine-fused diketopiperazines and hydantoins has been developed. The synthesis of these tetracyclic ring systems was initiated by an Ugi reaction, which brought together all necessary functionalities for further transformations. The Ugi adducts were then subjected to a base-induced ring closing and an intramolecular azide–alkyne cycloaddition reaction in succession to obtain highly fused benzodiazepine frameworks.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 77 publications
0
18
0
Order By: Relevance
“…Formation of 5a through propargylation followed by continuous heating for intramolecular click reaction affords product 6a . There are several reports in literature which demonstrated that intramolecular click reactions in one-pot synthesis could be achieved under Cu-free conditions [10,15,32,45,46].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Formation of 5a through propargylation followed by continuous heating for intramolecular click reaction affords product 6a . There are several reports in literature which demonstrated that intramolecular click reactions in one-pot synthesis could be achieved under Cu-free conditions [10,15,32,45,46].…”
Section: Resultsmentioning
confidence: 99%
“…Highly efficient and atom economic synthesis such as one-pot reactions and multicomponent reactions (MCRs) have gained increasing popularity in the synthesizing of complex molecules including triazolobenzodiazepine-type compounds [10,11,12,13,14,15]. For example, the Martin group reported a cascade reductive amination and intramolecular [3 + 2] cycloaddition reaction sequence for triazole-fused 1,4-benzodiazepines (Scheme 1A) [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, as highly methylated flavonoid derivatives [ 47 ] and 6-(3,5-dimethoxyphenyl)chromenes [ 48 49 ] have been demonstrated to be potent anti-seizure drugs and anticancer agents, respectively, a Suzuki–Miyaura reaction was performed yielding 13 in 51% yield. Since aldehydes are interesting and versatile functional moieties for further derivatization, e.g., used in the synthesis of heterocyclic scaffolds [ 33 34 50 ], several multicomponent reactions [ 40 , 51 – 53 ], etc . , we wished to convert dimethyl acetal 5j into aldehyde appended triazolochromene 14 and at the same time examine the stability under strong acidic conditions.…”
Section: Resultsmentioning
confidence: 99%
“…This characteristic feature is very efficient for MCR. We initially started optimization with symmetric imidazolium salts ([BBIM]Br, [BBIM]BF4), these ionic liquids were selected according to literature reports [14][15][16].…”
Section: Introductionmentioning
confidence: 99%